Field Testing a Research-Based Enrichment Module to Improve Students' Cognitive Learning Outcomes in Biodiversity - Arlika, Herlin; Anggun, Diah Putri; Yanti, Anita Andri (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The research-based enrichment module is a teaching material designed from recent studies and aligned with relevant learning content. This module aims to enrich students’ knowledge, improve their critical thinking skills, and enhance their understanding of current scientific concepts. This study investigated the effectiveness of a research-based enrichment module on karamunting plant identification in improving students’ learning outcomes. An experimental design with a pretest-posttest control group was applied. The population included 157 Grade X students at SMK Pertanian Pembangunan Negeri Sembawa. Using cluster sampling, 30 students from Grade X ATP 1 (control) and 30 from Grade X ATP 2 (experimental) were selected. The experimental group used the enrichment module, while the control group did not use any additional learning materials. Data were collected through cognitive learning outcome tests and analysed using descriptive statistics and a paired sample t-test. Results showed the experimental group achieved a mean post-test score of 81.67, compared to 70.50 in the control group. The paired sample t-test indicated a significant effect (p = 0.000, p 0.05). Thus, the enrichment module on karamunting identification significantly improved students’ cognitive learning outcomes.